No bejel among Surinamese, Antillean and Dutch syphilis diagnosed patients in Amsterdam between 2006-2018 evidenced by multi-locus sequence typing of Treponema pallidum isolates - Zondag, Hélène C A; Bruisten, Sylvia M; Vrbová, Eliška; Šmajs, David (PLoS One, 2020)
BACKGROUND: Treponema pallidum subspecies pallidum (TPA) and subsp. endemicum (TEN) are the causative agents of syphilis and bejel, respectively. TEN shows similar clinical manifestations and is morphologically and serologically indistinguishable from TPA. Recently, bejel was found outside of its assumed endemic areas. Using molecular typing we aimed to discover bejel and characterize circulating TPA types among syphilis cases with Surinamese, Antillean and Dutch ethnicity in Amsterdam. METHODS: DNA was extracted from 137 ulcer swabs, which tested positive in the in-house diagnostic PCR targeting the polA gene. Samples were collected between 2006 and 2018 from Surinamese, Antillean and Dutch patients attending the Amsterdam STI clinic. Multilocus sequence typing was performed by partial sequence analysis of the tp0136, tp0548 and tp0705 genes. In addition, the 23S rRNA loci were analyzed for A2058G and A2059G macrolide resistance mutations. RESULTS: We found 17 distinct allelic profiles in 103/137 (75%) fully typed samples, which were all TPA and none TEN. Of the strains, 82.5% were SS14-like and 17.5% Nichols-like. The prevalence of Nichols-like strains found in this study is relatively high compared to nearby countries. The most prevalent types were 1.3.1 (42%) and 1.1.1 (19%), in concordance with similar TPA typing studies. The majority of the TPA types found were unique per country. New allelic types (7) and profiles (10) were found. The successfully sequenced 23S rRNA loci from 123/137 (90%) samples showed the presence of 79% A2058G and 2% A2059G mutations. CONCLUSIONS: No TEN was found in the samples from different ethnicities residing in Amsterdam, the Netherlands, so no misdiagnoses occurred. Bejel has thus not (yet) spread as a sexually transmitted disease in the Netherlands. The strain diversity found in this study reflects the local male STI clinic population which is a diverse, mixed group.
Keywords: dospělí; taxonomické DNA čárové kódování; DNA Barcoding, Taxonomic; etnicita; Netherlands; Ethnicity; Adult; Suriname; bakteriální geny; lidé; syfilis; Surinam; Netherlands Antilles; Nizozemsko; Nizozemské Antily; alely; Syphilis; Alleles; Genes, Bacterial; Treponema pallidum; Humans